Tumor biological profile of patients up to 50 years of age in an inland city of São Paulo - Corregliano, Mariana Rossi; Cintra, Karine Angélica; Kirchhoff, Barbara Mendes; Martins, Stella Souza; Silva, Rodrigo Tavares (Mastology, 2021)
Introduction: In Brazil, breast cancer screening is not performed in young women. However, although less frequent, the disease is generally more aggressive in this age group, with worse prognosis and refractoriness to treatment. Thus, the identification of specific subtypes by immunohistochemistry can help improve the effectiveness of treatments. Objectives: To evaluate the biological characteristics of breast tumors in patients under 50 years. Methods: This is an observational, longitudinal, retrospective study, based on data collected from medical records of the Hospital do Câncer de Franca, from January 2015 to February 2018. Results: The most frequent biological subtype was luminal B (42.5%), and the mean age of the women was 43.6 years. The most prevalent clinical staging was IIA (31%). Mastectomy with axillary drainage was the most used surgical treatment. A positive correlation was found between biological profiles and sociodemographic data, with a predominance of the luminal B subtype in women under 40 years and luminal A in those between 41 and 50 years. The mean tumor size was 4.2 cm, being larger in older and white patients. In multiparous women, the subtypes HER2 and luminal A and B stood out. Conclusion: Luminal B and luminal A biological profiles, as well as staging II and III, were the most prevalent. Mastectomy and axillary drainage were the most common surgical treatments. The employment of these procedures should be reviewed by the service in order to improve the quality of life of the patients treated, favoring the expansion of primary conservative surgeries or post-neoadjuvant chemotherapy.